A Perspective on Nrf2 Signaling Pathway for Neuroinflammation: A Potential Therapeutic Target in Alzheimer's and Parkinson's Diseases - Saha, Sarmistha; Buttari, Brigitta; Profumo, Elisabetta; Tucci, Paolo; Saso, Luciano (Frontiers in Cellular Neuroscience, 2022)
Neuroinflammation plays a pivotal role in Alzheimer's disease (AD) and Parkinson's disease (PD), the leading causes of dementia. These neurological disorders are characterized by the accumulation of misfolded proteins such as amyloid-ß (Aß), tau protein and α-synuclein, contributing to mitochondrial fragmentation, oxidative stress, and neuroinflammation. Misfolded proteins activate microglia, which induces neuroinflammation, expression of pro-inflammatory cytokines and subsequently facilitates synaptic damage and neuronal loss. So far, all the proposed drugs were based on the inhibition of protein aggregation and were failed in clinical trials. Therefore, the treatment options of dementia are still a challenging issue. Thus, it is worthwhile to study alternative therapeutic strategies. In this context, there is increasing data on the pivotal role of transcription factor NF- E2 p45-related factor 2 (Nrf2) on the redox homeostasis and anti-inflammatory functions in neurodegenerative disorders. Interestingly, Nrf2 signaling pathway has shown upregulation of antioxidant genes, inhibition of microglia-mediated inflammation, and improved mitochondrial function in neurodegenerative diseases, suggesting Nrf2 activation could be a novel therapeutic approach to target pathogenesis. The present review will examine the correlation between Nrf2 signaling with neuroinflammation in AD and PD.